The analysis of BUMDes management and its contribution towards village genuine income: a study on BUMDes Pamsimas Sendang Sari Desa Kunir - Suryani, Pesi; Daurrohmah, Eka Wirajuang (Universitas Widya Mataram, 2023)
The study aimed at exploring deeply the business management and process of BUMDes Pamsimas Sendang Sari Desa Kunir and its contribution towards the village's genuine income (read: Pendapatan Asli Desa or PAD). The research used descriptive qualitative methodology with a semi-structured interview. The five informants of the research were the staff of the BUMDes PAMSIMAS as the chief, secretary, treasurer, and two field technicians. The data analyzed was assisted by Computer Assisted Qualitative Data Analysis Software such as Nvivo 11. The research result showed that in the business process, BUMDes Sendang Sari has not to get profited from the clean water distribution since the setting of clean water tariffs below market prices, lack of public awareness to pay monthly fees, the existence of a village head program that makes clean water free for all public facilities without any subsidy, and the existence of a tax on water wells in Kabupaten Demak. Therefore, the BUMDes Sendang Sari is still unable to contribute to the PAD of Desa Kunir, however, the social impact has been felt by residents with the distribution of clean water to residents' homes. This research only focuses on business processes and has not looked at other factors that can affect the BUMDes performance. The research contribution of each of the village governments is as input for the management to fix the BUMDes Sendang Sari thus able to optimize the roles of the BUMDes in contributing towards the village's genuine income.